Análise exoproteômica comparativa do sobrenadante de uma cepa de Clostridium difficile isolada em um hospital cearense - Pacífico, Dvison de Melo (2018)
C. difficile, a Gram-positive, spore-forming anaerobic bacterium, is considered the leading cause of antibiotic-associated diarrhea in hospitalized patients worldwide, causing C. difficile infection (CDI). The main virulence factors of C. difficile are toxins A (TcdA) and B (TcdB), but others, such as surface layer proteins (SLPs) and flagellum, have also been described and related to the observed inflammatory responses in the CDI. The objective of this study was to identify these virulence factors and other proteins involved in the pathogenesis of CDI by comparative exoproteomics between the supernatant of a virulent strain, ICC-45, isolated in a hospital in the state of Ceará and to compare it with the strain NAP1/027 (LIBA5756) isolated in Costa Rica. After the growth of the C. difficile strains by an incubation period of 24h at 37ºC in the anaerobic jar, the secreted proteins were obtained and analyzed by the in solution technique that were later processed by the type mass spectrometry Nano-LC ESI-MS / MS coupled to LTQ-Orbitrap. From the analysis in solution, a total of 197 proteins were identified, of which 5 belong exclusively the ICC-45 strain. On the other hand, strains ICC-45 and NAP1/027 (LIBA5756) shared 192 proteins. Of the 192 shared proteins, 26 were selected and categorized into six groups (pathogenicity, antimicrobial resistance, heat shock and oxidative stress, nitric oxide, metabolism and other activities). Several proteins related to virulence factors that contribute positively to the pathogenicity of CDI were identified in greater quantity in the ICC-45 strain supernatant when compared to the strain NAP1/027 (LIBA5756). Among these proteins are TcdA and TcdB, S-layer protein, cell surface protein (Cwp19), cell wall proteins (Cwps), flagellin (FliC) and cysteine protease (Cwp84). In addition, other proteins related to the other categories (antimicrobial resistance, heat shock and oxidative stress, nitric oxide, metabolism and other activities) were also found in a larger quantity in the supernatant of the ICC-45 strain. The exclusive proteins of the ICC-45 strain are involved with the catalytic and binding functions. Among the proteins shared, most of them are linked with the catalytic functions, followed by the binding and toxin functions. Both, proteins unique to the ICC-45 strain and those shared between them, more than half are of cytoplasmic origin. Proteins from strains ICC-45 and NAP1 / 027 (LIBA5756) showed similar physical and functional interactions. The ICC-45 exclusive proteins indirectly interacts with the pathogenicity proteins (TcdA, TcdB, FliC, Cwp84 and SlpA) shared among the strains. In addition, the detection of higher amounts of certain proteins in the ICC-45 strain may have an impact on the pathogenesis and clinical parameters of the disease induced by this strain isolated in Northest of Brazil.